Sixty gigahertz indoor radio wave propagation prediction method based on full scattering model. Issue 4 (22nd April 2014) - Järveläinen, J.; Haneda, K.
<x xml:space="preserve">Abstract</x> In radio system deployment, the main focus is on assuring sufficient coverage, which can be estimated with path loss models for specific scenarios. When more detailed performance metrics such as peak throughput are studied, the environment has to be modeled accurately in order to estimate multipath behavior. By means of laser scanning we can acquire very accurate data of indoor environments, but the format of the scanning data, a point cloud, cannot be used directly in available deterministic propagation prediction tools. Therefore, we propose to use a single‐lobe directive model, which calculates the electromagnetic field scattering from a small surface and is applicable to the point cloud, and describe the overall field as fully diffuse backscattering from the point cloud. The focus of this paper is to validate the point cloud‐based full diffuse propagation prediction method at 60 GHz. The performance is evaluated by comparing characteristics of measured and predicted power delay profiles in a small office room and an ultrasonic inspection room in a hospital. Also directional characteristics are investigated. It is shown that by considering single‐bounce scattering only, the mean delay can be estimated with an average error of 2.6% and the RMS delay spread with an average error of 8.2%. The errors when calculating the azimuth and elevation spreads are 2.6° and 0.6°, respectively. Furthermore, the results demonstrate the applicability of a single parameter set to characterize the propagation channel in all transmit and receive antenna locations in the tested scenarios.